2017
DOI: 10.4103/ijccm.ijccm_281_16
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypertriglyceridemia Causing Pancreatitis in a Child with New-onset Type-I Diabetes Mellitus Presenting with Diabetic Ketoacidosis

Abstract: The triad of pancreatitis, hypertriglyceridemia, and diabetic ketoacidosis and its treatment has not been extensively discussed in the pediatric literature. We report a 4-year-old child with severe hypertriglyceridemia, pancreatitis, and diabetic ketoacidosis. Hypertriglyceridemia and pancreatitis with diabetic ketoacidosis can be successfully managed with insulin and hydration therapy in children. Early recognition of this triad is important as insulin requirements, recovery duration, and prognosis can be alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…Through a literature review of previous case reports, most severe hypertriglyceridemia is observed with DKA in patients recently diagnosed with type 1 diabetes or can be attributed to poor control of diabetes in patients with severe insulin deficiency (Table 4). 27‐29 DKA patients manifest with disorders of glucose and lipid metabolism, thereby leading to hypertriglyceridemia‐induced AP.…”
Section: Discussionmentioning
confidence: 99%
“…Through a literature review of previous case reports, most severe hypertriglyceridemia is observed with DKA in patients recently diagnosed with type 1 diabetes or can be attributed to poor control of diabetes in patients with severe insulin deficiency (Table 4). 27‐29 DKA patients manifest with disorders of glucose and lipid metabolism, thereby leading to hypertriglyceridemia‐induced AP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AP can be induced by diabetic ketoacidosis (DKA), complicated by hypertriglyceridemia [2]. However, and to the best of our knowledge, the association of this triad of pancreatitis, hypertriglyceridemia, and diabetic ketoacidosis and its treatment has not been widely discussed in the literature in both adults and children [3]. Rapid diagnosis is difficult due to overlapping signs, but it is crucial for adequate management.…”
Section: Introductionmentioning
confidence: 99%
“…In many case reports, severe HTG is observed during DKA associated with newly diagnosed T1D [5, 6] or attributed to poor diabetes control [7] with severe insulin deficiency. In our case, the fact that his HbA1c was 11.5% signifies insulin deficiency for months, even if he did not report discontinuing his insulin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of hypertriglyceridemia in DKA involves insulin deficiency which activate lipolysis in adipose tissue and increase the release of free fatty acid, which accelerate formation of very low-density lipoprotein by the liver [5]. Insulin deficiency is also associated with decreased activity of lipoprotein lipase (LPL), the enzyme responsible for TG metabolism, which reduces the clearance of VLDL and chylomicrons from the plasma, causing hypertriglyceridemia [8, 9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation